A new application of generalized quasi-power increasing sequences - Bor, H. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We prove a theorem dealing with |N, p_n, θ_n|_k-summability using a new general class of power increasing sequences instead of a quasi-η-power increasing sequence. This theorem also includes some new and known results.